2022
DOI: 10.1007/s11764-022-01267-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of APOE and smoking history on cognitive function in older, long-term breast cancer survivors

Abstract: To determine whether older breast cancer survivors score lower on neuropsychological tests compared to matched non-cancer controls and to test the hypotheses that survivors who were APOE ε4 carriers would have the lowest cognitive performance, but that smoking history would decrease the negative effect of ε4 on cognition. MethodsFemale breast cancer survivors who had been diagnosed and treated at age 60 or older and were 5 -15 year survivors (N=328) and age and education matched non-cancer controls (N=160) wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…Interestingly, the parent study from which the present neuroimaging substudy derived showed worse performance on all three domains of cognitive function, including language, executive function, and learning and memory, over time in the cancer survivors with or without chemotherapy but not in the non‐cancer controls. Similar to the FA data, the parent study found no significant differences in cognitive testing scores between the two cancer survivor groups 31 . Taken together, the FA values in the genu of the corpus callosum and the cognitive functioning of the three domains could potentially serve as markers for CRCI in older breast cancer survivors.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, the parent study from which the present neuroimaging substudy derived showed worse performance on all three domains of cognitive function, including language, executive function, and learning and memory, over time in the cancer survivors with or without chemotherapy but not in the non‐cancer controls. Similar to the FA data, the parent study found no significant differences in cognitive testing scores between the two cancer survivor groups 31 . Taken together, the FA values in the genu of the corpus callosum and the cognitive functioning of the three domains could potentially serve as markers for CRCI in older breast cancer survivors.…”
Section: Discussionsupporting
confidence: 64%
“…Similar to the FA data, the parent study found no significant differences in cognitive testing scores between the two cancer survivor groups. 31 Taken together, the FA values in the genu of the corpus callosum and the cognitive functioning of the three domains could potentially serve as markers for CRCI in older breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…While we note that generational cohort effects are of less concern given evidence that these effects have diminished, we cannot rule out any cohort effect on our analysis as a whole. As an example, tobacco use has steadily declined in successive generations and previous nicotine exposure has been associated with a potentially protective effect on cognition in APOE4+ carriers [ 35 ]. With the addition of control data from equivalent ages/cohorts, we can, however, control for any cohort effects that would influence differences in cognition between survivors and controls.…”
Section: Discussionmentioning
confidence: 99%
“…The data reported here were collected as part of a collaboration between Memorial Sloan Kettering Cancer Center and City of Hope (PIs: Ahles; Hurria) on a cohort study that assessed cognition in controls and breast cancer survivors (age 60 or greater) who were all at least five years post-treatment and were followed prospectively over two years with four timepoints at eight-month intervals [ 35 ]. In this secondary analysis, we examined data derived from the first time-point across a longer 5–15-year interval, in four quartiles, as a proxy indicator of how cognitive trajectories might be altered given a history of cancer and cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The data reported here was collected as part of a collaboration between Memorial Sloan Kettering Cancer Center and City of Hope (PIs: Ahles; Hurria) that assessed cognition in controls and breast cancer survivors (age 60 or greater) who were all at least 5 years post-treatment and followed prospectively over 2 years with 4 timepoints at 8-month intervals [35]. In this secondary analysis we examined data derived from the first timepoint across a longer 5 to 15 year interval, in 4 quartiles, as a proxy indicator of how cognitive trajectories might be altered given a history of cancer and cancer treatment.…”
Section: Introductionmentioning
confidence: 99%